Endoscopic Repair of Posterior Ankle Impingement Syndrome Due to Os Trigonum in Soccer Players. (January 2015) - López Valerio, Víctor; Seijas, Roberto; Alvarez, Pedro; Ares, Oscar; Steinbacher, Gilbert; Sallent, Andrea; Cugat, Ramón
Background: An os trigonum may cause posterior ankle impingement syndrome (PAIS), which may lead to poor sports performance, especially in soccer players. The aim of the present study was to analyze the outcomes of endoscopic repaired posterior ankle impingement (PAI) secondary to os trigonum syndrome within a group of soccer players as well as their return to play time. Methods: A retrospective review of 20 soccer players with Tegner activity level 9 was performed. All players were diagnosed of PAIS due to os trigonum. Chief complaint was pain produced with forced plantarflexion when kicking the ball. Conservative treatment was first performed during a 6-week rehabilitation program. When conservative treatment failed, arthroscopic surgical resection of the os trigonum was proposed. Visual analogue scale (VAS) was used to measure pain before and after surgery as well as time until their return to previous sports level. Results: VAS showed a mean preoperative pain score of 7.5 (SD = 0.9), whereas postoperative VAS at 1 month after surgery decreased to 0.8 (SD = 1.36). Mean symptomatic period was 8.5 months (SD = 4.3), from the beginning of symptoms up to the surgery day. Once patients had undergone surgery, mean time until their return to previous level of sports was 46.9 days (SD = 25.96), reaching the same pre-lesion Tegner level. Conclusions: Endoscopic treatment of posterior ankle impingement syndrome due to os trigonum showed excellent results. Hindfoot endoscopy with a posterior approach was an effective treatment and allowed for a prompt return to play in soccer players with a high activity level. Level of Evidence: Level IV, therapeutic study.